The cytotoxic synergy between Clostridioides difficile toxin B and proinflammatory cytokines: an unholy alliance favoring the onset of Clostridioides difficile infection and relapses - Gabrio Bassotti (MicrobiologyOpen, 2020)
Abstract Clostridioides difficile infection (CDI) represents an important health problem worldwide, with significant morbidity and mortality. This infection has also high recurrence rates, whose pathophysiological grounds are still poorly understood. Based on our experiments in vitro with Clostridioides difficile toxin B and existing experimental and clinical evidence, we propose that primary CDI and relapses might be favored by a mechanism that involves the enhancement of the toxicity of toxin B by proinflammatory cytokines, tumor necrosis factor alpha, and interferon gamma on the enteric glial cells and their network in an environment characterized by a strong dysmicrobism.